1997
DOI: 10.1111/j.1365-2923.1997.tb02467.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and learning in day surgery units: a UK survey

Abstract: Recent increases in day case surgery offer new opportunities for medical student learning, whilst the reduction in surgical beds and length of hospital stays has reduced opportunities in traditional inpatient settings. To establish the extent and nature of undergraduate medical education in day surgery units in the UK, the authors undertook a postal questionnaire survey. Of the 227 units which replied, 45% are used for teaching. In 83% of these, students attend only single operating lists, and only 7% of units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…One likely reason for this is that advances in surgical procedures and anaesthetics over the last decade have led to faster recovery times for patients, earlier hospital discharges, and increased day case and outpatient management. 5 The introduction of surgical teaching in the community is one possible solution.…”
Section: Introductionmentioning
confidence: 99%
“…One likely reason for this is that advances in surgical procedures and anaesthetics over the last decade have led to faster recovery times for patients, earlier hospital discharges, and increased day case and outpatient management. 5 The introduction of surgical teaching in the community is one possible solution.…”
Section: Introductionmentioning
confidence: 99%
“…This study has demonstrated that organised teaching in the DSU is appreciated by medical students. However, if students’ visits to the DSU occur only when shadowing a clinician undertaking service commitments, they are not likely to be as positive as when a structured teaching programme is used 3 …”
Section: Discussionmentioning
confidence: 99%
“…Teaching opportunities can be expanded in this setting, where facilities may be under‐utilised. Seabrook et al 3 found that only 45 per cent of 227 medical schools used the day surgery unit (DSU) for teaching. Dunnington and DaRosa 4 proposed highly structured learning modules in the DSU, where innovative teaching programmes could take place without compromising patient care 5 …”
mentioning
confidence: 99%
“…Recently there has been a growing awareness of the need for formal undergraduate education programmes incorporating principles and techniques unique to ambulatory surgery and anaesthesia 2 . 3 Opportunities for medical undergraduate programmes are now being sought and developed in the day surgery setting 4 . 5 It has been demonstrated that it is feasible for students to be attached to a day surgery facility without a negative impact on efficiency 6 .…”
Section: Introductionmentioning
confidence: 99%